Participatory Water Resource Management in the Context of Thailand - Tunma, Eakkarin; Sirisugandha, Thanakorn (Journal of Graduate MCU KhonKaen Campus, 2025)
Water resource management in Thailand has been mainly carried out by government agencies or community leaders in the past, with limited public participation. Problems have arisen, such as the lack of integration of water resource management policies, lack of budget, lack of public knowledge and awareness, and even problems resulting from climate change. However, the current trend in water resource management has begun to change, with greater emphasis on integration and public participation. The water resource management approach that should be given importance is to emphasize fair participation of communities and related persons to have sufficient water for consumption and use, to be self-reliant in water resources and to maintain the ecosystem and environment appropriately by restoring local wisdom, managing the entire watershed system, creating economic incentives, allowing every sector to express their opinions and play a role in policy-making or adjusting policies to support disasters such as drought or floods that are appropriate for the context of various communities in Thailand. This will result in sustainable water resource development.